AN ANALYSIS OF EXPECTANCY VALUES IN FRONT OF THE CLASS FILM - Fernando Novelius; Satyawati Surya; Nasrullah Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
ABSTRACTThis research intended to find the values of expectancy in Front of the Class film. The researcher analyzed the values of expectancy that depicted through Brad Cohen character and Cohen’s mother character. The data were analyzed with expectancy-value theory by Charles S. Carver and Michael F. Scheier. The data were generated from the dialogues and the actions of the characters in their struggle facing the adversity and to obtain their goals. In conclusion, this research revealed the values of expectancy that depicted from Brad Cohen character and Cohen’s mother character. Those are the goals that they had as a desirable and the values that Brad saw as undesirable. Also expectancy, that is sense of confidence from Brad Cohen and his mother about the eventual outcome of their efforts and sense of doubt from Brad Cohen about the eventual outcome of his efforts. Finally, the conclusion that can be drawn is that the findings in this research strengthen the fact that there are values of expectancy in Front of the Class film. Such as; Brad’s desire to be a teacher and all the concrete actions, also Cohen’s mother’s desire to cure Brad and to make Brad having a normal life and all the concrete actions to obtain it. Furthermore, the other findings of expetancy-value are those the refusal of Brad Cohen and Cohen’s mother to be different from people in a group of Tourette syndrome and also the refusal of Brad Cohen about an offer from Cohen’s father to be a building worker. Then, the sense of confidence of Brad Cohen and Cohen’s mother are also the values of expectancy. Those are sense of confidence about the eventual outcome of the struggle to be a teacher and the eventual outcome to cure Brad and to make Brad have a normal life, and also when Brad Cohen becomes doubtful about his effort to be a teacher.Key words: the values of expectancy, goals, expectancy ABSTRAKPenelitian ini bertujuan untuk menemukan nilai-nilai harapan (expectancy) dalam film Front of the Class. Peneliti menganalisis nilai-nilai harapan (expectancy) yang tergambarkan melalui tokoh Brad Cohen dan tokoh ibu Cohen. Data dianalisis dengan teori nilai harapan (expectancy-value) oleh Charles S. Carver dan Michael F. Scheier. Data tersebut dihasilkan dari dialog-dialog dan tindakan-tindakan dari tokoh-tokoh tersebut dalam perjuangan mereka menghadapi kemalangan dan perjuangan mereka untuk menggapai tujuan-tujuan mereka. Kesimpulannya, penelitian ini mengungkapkan nilai-nilai harapan yang tergambarkan dari tokoh Brad Cohen dan tokoh ibu Cohen. Yaitu tujuan-tujuan yang mereka miliki sebagai sesuatu yang diinginkan dan nilai-nilai yang Brad lihat sebagai sesuatu yang tidak diinginkan, dan juga harapan, yaitu rasa percaya diri dari Brad Cohen dan ibunya terhadap hasil akhir dari usaha-usaha mereka dan rasa ragu dari Brad Cohen terhadap hasil akhir dari usaha-usahanya. Akhirnya, kesimpulan yang dapat ditarik adalah bahwa temuan dalam penelitian ini memperkuat fakta bahwa terdapat nilai-nilai harapan dalam film Front of the Class. Seperti; hasrat Brad untuk menjadi seorang guru dan semua tindakan-tindakan  konkritnya, juga hasrat ibu Cohen untuk menyembuhkan Brad dan untuk membuat Brad memiliki kehidupan yang normal dan semua tindakan-tindakan konkrit untuk menggapainya. Lebih lagi, penemuan-penemuan Expectancy-value  lainnya adalah penolakan dari Brad Cohen dan ibu Cohen untuk menjadi berbeda dari orang-orang dalam sebuah kelompok Tourette syndrome dan juga penolakan dari Brad Cohen terhadap tawaran dari ayah Cohen untuk menjadi seorang pekerja bangunan. Lalu, rasa percaya diri dari Brad Cohen dan ibu Cohen adalah juga nilai-nilai dari expectancy. Yaitu rasa percaya diri terhadap hasil akhir dari perjuangan untuk menjadi seorang guru dan hasil akhir untuk menyembuhkan Brad dan untuk membuatnya memiliki kehidupan yang normal, dan juga ketika Brad Cohen menjadi ragu terhadap usahanya untuk menjadi seorang guru.Kata kunci:     Nilai-nilai harapan, tujuan-tujuan, harapan